2016
DOI: 10.1016/j.jad.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Attentional biases in problem and non-problem gamblers

Abstract: Background: From a cognitive perspective, attentional biases are deemed as factors responsible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 42 publications
7
48
3
1
Order By: Relevance
“…In NPGs, no difference between attentional detection of neutral and gambling-related stimuli was found, and was therefore in line with results of past studies showing that no attentional bias is observable in the absence of problem gambling (e.g., Brevers et al, 2011aBrevers et al, , 2011bCiccarelli et al, 2016;Wolfling et al, 2011). PGs took less time to respond when presented with gambling-related pictures in the early orientation of attention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In NPGs, no difference between attentional detection of neutral and gambling-related stimuli was found, and was therefore in line with results of past studies showing that no attentional bias is observable in the absence of problem gambling (e.g., Brevers et al, 2011aBrevers et al, , 2011bCiccarelli et al, 2016;Wolfling et al, 2011). PGs took less time to respond when presented with gambling-related pictures in the early orientation of attention.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to this, Ciccarelli et al (2016) study found a facilitation bias in reacting to gambling-related stimuli only in the initial orienting of attention among problem gamblers.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies (e.g. refs 51 and 52), these were non-problem gamblers that scored 0–2 (n = 978), gamblers at risk with a score equal to 3-4 (n = 87), and problem gamblers that scored 5–20 (n = 55) with the maximum being 13 in the present sample. Most of the forms of gambling among the gamblers are mahjong, poker cards, and lottery, because casino games are legally prohibited in whole Mainland China, in accordance with that in our previous study59.…”
Section: Methodssupporting
confidence: 92%
“…To better reflect the taxonomy of gambling behavior and elucidate the potential role of psychological and neurocognitive components in the development from recreational gambling to problem gambling, two recent studies used a non-dichotomous classification of gambling disorder comparing people with PG to those at an increased risk of developing PG (i.e., at-risk PG) as well as those with no risk of PG ((i.e., no-risk PG) on tasks of attentional bias51, and response inhibition and cognitive flexibility52. Impaired response inhibition and cognitive flexibility were found in PG compared with at-risk and no-risk PG, and differences on attentional biases were not significant between PG and at-risk PG, but significant between PG and no-risk PG.…”
mentioning
confidence: 99%